2017
DOI: 10.1149/07522.0053ecst
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Ion Transport in Glyme-Based Electrolyte Solutions for Li-Air Batteries

Abstract: To clarify the relationship between ion transport behavior and Li deposition/dissolution reaction at Li metal negative electrode (NE) for Li-air batteries, 1.0 M of LiSO 3 CF 3 /tetraglyme(G4) and LiN(SO 2 CF 3 ) 2 /G4 electrolytes were selected, and the Li + transport were evaluated from two aspects, i.e. i) Li + supplying rate to the Li metal NE and ii) charge transfer rate through solid state interphase (SEI) films at Li metal NE. For the former aspect, self-diffusion coefficients D of Li + , anion and G4 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…These results suggested that a suitable anode-surface oxidation may enhance the electrode/electrolyte interface characteristics. 116,120 The electrolyte formulation and the electrochemical conditions may affect both kinetics and thermodynamics of ORR, for instance by altering the solvation in high DN solvents. Along with solvent DN, the level of dissociation of the salt may have additional contributions in determining the characteristics of ORR and controlling the morphology of Li 2 O 2 deposits, as schematically illustrated in Figure 8d.…”
Section: "Glyme" Electrolyte In Li-o 2 Battery: the Upcoming Futurementioning
confidence: 99%
See 1 more Smart Citation
“…These results suggested that a suitable anode-surface oxidation may enhance the electrode/electrolyte interface characteristics. 116,120 The electrolyte formulation and the electrochemical conditions may affect both kinetics and thermodynamics of ORR, for instance by altering the solvation in high DN solvents. Along with solvent DN, the level of dissociation of the salt may have additional contributions in determining the characteristics of ORR and controlling the morphology of Li 2 O 2 deposits, as schematically illustrated in Figure 8d.…”
Section: "Glyme" Electrolyte In Li-o 2 Battery: the Upcoming Futurementioning
confidence: 99%
“…Notably, this system could store even more energy than the Li–S cell and has been suggested as a possible battery for future applications. 105–130 In this review, we discuss with chronological details various developments in the research on glyme-based electrolytes for lithium batteries, which are summarized in the scheme in Fig. 1 (panel a).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we investigated the Li dissolution/deposition reaction at the glyme electrolyte side, including the formation of SEI films on the Li metal NEs, to understand the factors affecting the Li dendrite growth. 18 Figure 1 shows a schematic illustration of the interface between the Li metal NE and the glyme electrolyte used in LAB systems. The Li deposition/dissolution reaction is thought to be controlled by two aspects, namely: i) a Li + supply process to the Li metal NE; and ii) a Li + charge transfer process through the SEI films on the surface of the Li metal NE.…”
mentioning
confidence: 99%